How to lose a guy in 10 days [videorecording (DVD)] - Petrie, Donald; Hudson, Kate, 1979-; McConaughey, Matthew, 1969-; Goldberg, Adam, 1970-; Neuwirth, Bebe; Alexander, Michele (Paramount, 2003)
Andi is the "How to" girl at an up-and-coming women's magazine who needs to prove she can pick up any guy and dump him in 10 days. And in order for Ben to win an advertising presentation he needs to prove he can make any woman fall in love with him in 10 days. Now that they are a "couple" and the clock is ticking, anything goes ...